Nephrectomy in metastatic renal cell carcinoma with venous thrombus: more thrombus equals less benefit? - Burotto, Mauricio; Renner, Alex (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Complete surgical resection of the tumor by means of either partial or total nephrectomy is the only curative therapy for localized renal cell carcinoma (RCC). However, as we move into the metastatic setting (mRCC), nephrectomy was historically limited to a palliative role, in efforts to control pain, hematuria or paraneoplastic syndromes. This changed in 2001 when two randomized trials comparing interferon alone versus nephrectomy followed by interferon showed an overall survival (OS) advantage for the surgery arm (1,2) which led to a significant increase in the proportion of mRCC patients undergoing nephrectomy, reaching almost 40% of cases by 2004 (3). Fast forward to 2018, the first prospective study on nephrectomy in the targeted therapy era becomes available, showing that nephrectomy does not increase OS in this setting, as systemic treatment with sunitinib resulted in non-inferior OS compared to surgery followed by sunitinib in the CARMENA (Cancer du Rein Metastatique Nephrectomie et Antiangiogéniques) trial (4).